Determination of Factors Affecting the Incidence of Anemia in Pregnant Women - Leny Blegur; Iin Inayah; Murtiningsih Murtiningsih; Tetty Solehati; Monna Maharani Hidayat (Indonesian Journal of Global Health Research, 2025)
Anemia in pregnant women remains a global health problem, including in Timor Leste, where its prevalence is notably high. This study aimed to analyze the factors influencing the incidence of anemia among pregnant women at Centro Saude Komunitaria Becora, Dili. A quantitative study was conducted using an analytical cross-sectional design. The study population comprised all pregnant women diagnosed with iron deficiency anemia in July 2025, totaling 115 individuals, all of whom were included as respondents using a total sampling technique. Data were collected through a structured questionnaire tested for validity (p < 0.05) and reliability (Cronbach’s Alpha = 0.838). Variables examined included maternal age, parity, education, income, ANC visit frequency, knowledge level, compliance with iron supplementation, and anemia status based on hemoglobin levels (<11 g/dL). Data were analyzed using univariate statistics for frequency distribution, bivariate analysis with Chi-Square tests, and multivariate analysis using binary logistic regression (95% CI; p < 0.05). Results revealed six significant factors: age, parity, education, income, ANC visit frequency, and knowledge. High parity (multiparity) emerged as the dominant risk factor (OR = 43.560), while other factors were protective. In conclusion, anemia in pregnant women is more strongly influenced by sociodemographic and behavioral factors than by supplementation compliance alone. Therefore, interventions should emphasize nutrition education, strengthening ANC services, economic empowerment, and optimal birth spacing strategies.